2020
DOI: 10.1111/jocs.14905
|View full text |Cite
|
Sign up to set email alerts
|

Impact of additional annuloplasty on tricuspid valve and cardiac functions after atrial septal defect closure in adults

Abstract: Background: Surgical indications for moderate to severe tricuspid regurgitation (TR) during atrial septal defect (ASD) closure are still unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Concomitant TV intervention associated with either RV pressure or volume overload in congenital heart disease has led to controversial conclusions in previous reports. 13 , 33 , 34 Most recent studies have shown TV repair offers significant reduction of TR with little added morbidity, 13 , 21 , 24 therefore supporting more proactive surgical management of significant concomitant TR. Indeed, RV volume or pressure overload as the underlying etiology for TV disease was not associated with TV reintervention, TR deemed moderate or greater at a follow-up, or mortality, and these patients overall did well with repair in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant TV intervention associated with either RV pressure or volume overload in congenital heart disease has led to controversial conclusions in previous reports. 13 , 33 , 34 Most recent studies have shown TV repair offers significant reduction of TR with little added morbidity, 13 , 21 , 24 therefore supporting more proactive surgical management of significant concomitant TR. Indeed, RV volume or pressure overload as the underlying etiology for TV disease was not associated with TV reintervention, TR deemed moderate or greater at a follow-up, or mortality, and these patients overall did well with repair in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Other etiologies, such as TV diseases related to right heart volume or pressure overload from intracardiac shunts, right ventricular outflow tract obstruction (RVOTO), iatrogenic TV injury, and isolated congenital TV disease have been described but remain relatively understudied. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Comprehensive studies on TV surgery remain rare and thus little data exist describing the surgical indications, outcomes, and prognostic factors for patients without Ebstein, single-ventricle (SV), or ccTGA lesions. We describe these elements for patients with non-Ebstein TV lesions in the setting of biventricular physiology and a right-sided TV.…”
mentioning
confidence: 99%